Aspects of choral self-referentiality in Euripides’ Iphigenia at Aulis - Πιπεριάς Παύλος (Ariadne, 2021)
IN THIS paper, I focus on aspects of choral self-referentiality. I draw attention to the intratextual pointers referring to the play’s choreia, giving prominence to the nexus between the ancient text as such and its performativity. The first case of choral self-referentiality that I discuss occurs in the Parodos of the play (vv. 206–230), where the Chorus describe the athletic race between Achilles and the Eumelus’ chariot. Another case of choral self-referentiality can be found in the Third Stasimon (vv. 1036–1057), where the Chorus project the choruses of the Pierides Muses and the Nereids through their own choreia.